Cards on the Table: Critical Reflections on a Participatory Research Method - Hope, Sophie; Mulhall, Henry (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This article critically reflects on the limitations and challenges of using Cards on the Table (COTT), a participatory research method used to evaluate experiences of participation in art projects. The focus of this article is on the application of COTT as part of our evaluation of BE PART, a four-year Creative Europe Program of the European Union that ran from 2019 to 2023. The COTT method is informed by community research and participation action research, but here we highlight the ambiguous and messy nature of researching with such a broad and varied network of communities. We illustrate the tension between our desire to research in a co-productive, community-led, and action-oriented way and the realities of conducting research with a vast network of participants and limited time and budget.